2017
DOI: 10.1002/gcc.22485
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the genes BRD8 and PHF1 in endometrial stromal sarcoma

Abstract: We present a new endometrial stromal sarcoma (ESS)‐associated genomic rearrangement involving chromosome arms 5p and 6p and leading to the formation of a BRD8‐PHF1 fusion gene. The PHF1 (PHD finger protein 1) gene, from 6p21, is known to be rearranged in ESS in a promiscuous way inasmuch as it has been shown to recombine with JAZF1, EPC1, MEAF6, and now also with BRD8, in tumors of this type. In all rearrangements of PHF1, including the present one, a recurrent theme is that the entire coding part of PHF1 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…The first chromosomal rearrangement described in LG‐ESS was involved in chromosomes 7 and 17, leading to a fusion between JAZF1 (7p15) and SUZ12 (17q11.2) 11 . Later, other fusions were described, including rearrangements involving PHF1 and multiple partners, such as JAZF1 (7p15), EPC1 (10p11), 12 MEAF6 (1p34), BRD8 (5q31), EPC2 (2q23), and MBTD1‐EZHIP , associated with der(2)t(X;22)(p11;q13) 13‐15 . Described fusion partners for SUZ12 include MEAF6 16 and EPC1 17 …”
Section: Discussionmentioning
confidence: 99%
“…The first chromosomal rearrangement described in LG‐ESS was involved in chromosomes 7 and 17, leading to a fusion between JAZF1 (7p15) and SUZ12 (17q11.2) 11 . Later, other fusions were described, including rearrangements involving PHF1 and multiple partners, such as JAZF1 (7p15), EPC1 (10p11), 12 MEAF6 (1p34), BRD8 (5q31), EPC2 (2q23), and MBTD1‐EZHIP , associated with der(2)t(X;22)(p11;q13) 13‐15 . Described fusion partners for SUZ12 include MEAF6 16 and EPC1 17 …”
Section: Discussionmentioning
confidence: 99%
“…PHF1 was first reported as a neoplasia-associated fusion partner in low-grade endometrial stromal sarcomas in which rearrangements of the chromosomal band 6p21 generated the JAZF1-PHF1 and EPC1-PHF1 fusion genes (27). Furthermore, MEAF6-PHF1, BRD8-PHF1, and EPC2-PHF1 fusions have been reported in low-grade endometrial stromal sarcomas (28)(29)(30)(31). Recurrent rearrangement of the PHF1 gene and the fusion genes EP400-PHF1, EPC1-PHF1, and MEAF6-PHF1 have also been reported in ossifying fibromyxoid tumors (17,18,32) and a JAZF1-PHF1 and an AFF3-PHF1 fusion gene have been reported in an unusual ossifying sarcoma of the heart and a myxofibrosarcoma, respectively (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Micci et al show that the PHD finger protein 1 ( PHF1 ) gene from chromosomal band 6p21 recombined with JAZF1 as the partner gene of the JAZF1 gene in LG‐ESS. Further studies have shown that the PHF1 gene from chromosomal band 6p21 recombined with JAZF1 , EPC1 , MEAF6 or BRD8 , which encode the proteins involved in regulation of protein acetylation and/or histone acetyltransferase activity . All these fusions in ESS combined genes are involved in transcriptional regulation; that is, polycomb group complex‐mediated aberration methylation/acetylation; hence, their presumed oncogenic effects may be involved in the pathogenesis of ESS …”
Section: Endometrial Stromal Sarcomamentioning
confidence: 99%
“…Further studies have shown that the PHF1 gene from chromosomal band 6p21 recombined with JAZF1, EPC1, MEAF6 or BRD8, which encode the proteins involved in regulation of protein acetylation and/or histone acetyltransferase activity. 53 All these fusions in ESS combined genes are involved in transcriptional regulation; that is, polycomb group complex-mediated aberration methylation/acetylation; hence, their presumed oncogenic effects may be involved in the pathogenesis of ESS. 52 Currently, ESS is considered to be a tumor with molecular genetic heterogeneity in gene rearrangement.…”
Section: Molecular Biomarker Candidates For Diagnosis and Prognosismentioning
confidence: 99%